Optimization of Sb2(S, Se)3 photoabsorbers for photoelectrochemical hydrogen evolution reaction - Lee, Kian Jie (Nanyang Technological University, 2024)
Antimony chalcogenides is an excellent photoabsorber candidate for scalable photoelectrochemical water splitting. This is due to their unique characteristics, such as tuneable band gap, quasi-1D crystal structure, appropriate band alignment for water splitting, a stable single orthorhombic phase, low cost and non-toxicity. Efficient charge transport in antimony chalcogenides relies on a preferred growth orientation due to their anisotropic electrical conductivity. However, many studies have been conducted on antimony chalcogenide deposited on top of n-type material to achieve preferred orientation. This report focuses on the final performance of a photoelectrochemical device where antimony chalcogenide is deposited on top of p-type material. Hence, the effect of annealing temperature on the antimony chalcogenide photoabsorber as a function of percentage of selenium was investigated. The annealing temperature did not affect the preferred growth orientation of (hk1) over (hk0) plane for samples with 0% Se and no significant trend could be observed for samples with 30% Se. However, there was a preferred growth orientation of (hk1) over (hk0) plane for the samples with 10% Se when annealing temperature increased, and vice versa for the samples with 20% Se. Moreover, all antimony chalcogenide films show compact morphology without any presence of the pinholes. Additionally, the ratio of selenium to sulphur increased when the annealing temperature increased. Lastly, PEC measurements were conducted after the device fabrication to obtain the photocurrent of the device. Based on the results obtained, the photocurrent of the devices did not show any trend related to the annealing temperature but increased as the percentage of Se increased. The results of this report show that antimony chalcogenide with 20% Se and annealed at 300 °C provides optimal performance for the device, achieving 2.55 mA/cm2, comparable with other solution-processed S-rich antimony chalcogenide photocathodes.